Awakenings in triplicate: in ontogeny, after immobility, and to the presence of a congener. Comments on Ilan Golani’s concept of the mobility gradient - Kortmulder, Koenraad (Frontiers in Behavioral Neuroscience, 2024)
After a brief introduction on Ilan Golani's new approach to behavior, I offer an 'anatomical' description of the lateral display of a Cyprinid fish: Pethia nigrofasciata. I show how the display may have originated phylogenetically from a number of overlapping spinal reflexes which belong to the normal locomotion pattern. Next, I sketch the genesis of the concept of behavioral expansion, and illustrate it with a description of the full reproductive behavior of the same species as above. I conclude that, as in other examples studied by Golani, complexity increases as the spawning behavior unfolds in time. Finally, I sketch the concept of congener, and add some suggestions for follow-up studies, particularly such as are concerned with the sensory side.